DEVELOPMENT OF ONLINE CONTEXTUAL LEARNING MODELS USING A SCIENTIFIC APPROACH - Beta tivi (Universitas Lambung Mangkurat, 2021)
This study aims to describe the science-based contextual learning model applied in kindergarten in North Banjarbaru District during the pandemic, by adopting the type of development research. The tool used in this research is a science-based contextual learning tool developed by the researcher, so the tool must be tested before being used. Based on the findings, it is known that so far teachers have not designed learning tools according to the 2013 curriculum, where in the curriculum there are six aspects of development that must be carried out, including aspects of religious and moral values, social emotional, cognitive, language, physical motor, and art. . Where in presenting the themes and sub-themes, it must refer to these six aspects by presenting them in an integrated manner, it means linking the indicators developed in these aspects related to the sub-themes that have been selected or determined. The learning implementation plan made by the teacher only contains an assessment sheet in the form of a checklist, while to find out all aspects of child development, several assessment techniques are needed when the teacher provides learning and observes children while in the school environment.